(untitled) (International Association of Biologicals and Computational Digest, 2022)
Ayurveda had classified selected plants under "Madhya Rasayana". These are used both in herbal and conventional medicine and offer benefits that pharmaceutical drugs lack, helping to combat illness and support the body’s efforts to regain good health and intellect. In the present study production of phytoactive substances of such well known memory enhancing medicinal plant of Indian origin Centellaasiatica L. Urban was attempted through tissue culture and protocol for in vitro regeneration of plantlets. Leaf and Node explant of C. asiatica cultured on MS basal medium containing 3 mg/l IBA and 3 mg/l kinetin gave maximum proliferation of callus. Triterpenoidsare the important phytoactive substances of the C. asiatica used to increase mental ability.Attempt was made to produce triterpenoids of C. asiatica in vitro. In vivo and in vitro produced triterpenoids were compared using HPTLC. Substances with Rf. 0.09, 0.11, 0.19, 0.24, 0.29, 0.32, 0.43, 0.54, 0.66 and 0.78 were common in both in vivo and in vitro whichwas later confirmed by absorption spectra. Substances with Rf. 0.05 and 0.70 were only restricted to in vitro.